An Analysis on Stability and Deposition Zones of Natural Gas Hydrate in Dongsha Region, North of South China Sea. (16th February 2010) - Chen, Zuan; Bai, Wuming; Xu, Wenyue; Jin, Zhihe
Abstract : We propose several physical/chemical causes to support the seismic results which find presence of Bottom Simulating Reflector (BSR) at site 1144 and site 1148 in Dongsha Region, North of South China Sea. At site 1144, according to geothermal gradient, the bottom of stability zone of conduction mode is in agreement with BSR. At site 1148, however, the stability zone of conduction mode is smaller than the natural gas presence zone predicted by the BSR. We propose three causes, that is, mixed convection and conduction thermal flow mode, multiple composition of natural gas and overpressure in deep sediment to explain the BSR presence or gas hydrate presence. Further, our numerical simulation results suggest yet another reason for the presence of BSR at site 1144 and site 1148. Because the temperatures in deep sediment calculated from the mixed convection and conduction thermal flow mode are lower than that from the single conduction mode, the bottom of gas hydrate stability zone (GHSZ) is deeper than the bottom of gas hydrate deposition zone (GHDZ) or BSR. The result indicates that occurrence zone of natural is decided by the condition that natural gas concentrate in the zone is greater than its solubility.